Performance and Carbon Footprint Evaluation of a PWA-Based Waste Bank Information System - Muhammad Dzulfiqar; Adzanil Rachmadhi Putra; Rosyid Abdillah (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
The increasing volume of unmanaged waste in Indonesia has encouraged the adoption of digital waste bank management systems. However, the environmental impact of digital transformation, particularly regarding energy consumption and carbon emissions, remains insufficiently explored in community-scale information systems. This study evaluates the performance and environmental efficiency of Sibanksa, a Progressive Web Application (PWA)-based Waste Bank Information System, based on Green IT principles. A quantitative descriptive approach was applied by measuring four indicators: system performance, data transfer efficiency, estimated energy consumption, and digital carbon footprint under cached and non-cached loading scenarios. The results demonstrate that service worker caching significantly reduced data transfer size from an average of 4.84 MB to 20.9 kB, decreased estimated energy consumption from 0.0000594 kWh to 0.0000547 kWh, and reduced estimated carbon emissions from 0.044456 g CO₂ to 0.040886 g CO₂, representing approximately 8% improvements. Nevertheless, the overall page size remained relatively high (8.12 MB without caching and 7.46 MB with caching), while mobile rendering performance indicators, including First Contentful Paint (FCP) and Largest Contentful Paint (LCP), did not satisfy Web Vitals recommendations. This study contributes a practical measurement framework that integrates web performance analysis, energy efficiency assessment, and digital carbon footprint estimation for waste bank management systems. The findings provide empirical insights for developing more sustainable PWA-based information systems aligned with Green IT principles.